Simulation of a chirped femtosecond relativistic laser pulse interaction with underdense plasma by using a hydrodynamic approach. Issue 10 (2nd August 2019) - Li, Gang; Zhu, Bin; Wu, Yuchi; Lu, Feng; Tan, Fang; Zhang, Tiankui; Yang, Yue; Yu, Minghai; Yan, Yonghong; Fan, Wei; Gu, Yuqiu
Abstract: A chirped laser pulse indicates that the laser frequency changes over the duration of the pulse: a positively (negatively) chirped pulse implies that the laser frequency increases (decreases) with time. In this paper, we use a simplified, fully relativistic hydrodynamic approach to simulate the influence of chirp on the propagation of a femtosecond relativistic laser pulse in underdense plasma. Based on this simplified cold‐fluid model, the influence of chirp on the main dynamics of the laser pulse, such as self‐steepening, red‐shift in the leading edge, variation of the frequency chirp, and the generated wakefields can be studied self‐consistently. The simulation results show that a pulse with a positive chirp results in a larger increment in the intensity parameter a 0 when propagating a certain distance into an underdense plasma compared with an un‐chirped and a negatively chirped pulse, which is largely because of a much greater forward shift of the peak amplitude and more severe pulse self‐steepening effect due to the frequency red‐shift at the leading edge when exciting a plasma wave. The ponderomotive force, which relates to the first‐order differential of the laser pulse intensity envelope, is expected to be stronger for a positively chirped pulse because of its steeper leading edge and larger intensity parameter a 0 . As a result, the wakefield driven by the positively chirped laser pulse is more intense than that driven by an un‐chirped and a negatively chirped laser pulse, which is confirmed by our self‐consistent hydrodynamic simulation.